Quando vestir é mediar : experiência e afeto na e pela roupa - Ana Carolina Antunes Santos (2016)
In the present essay we consider clothing to be a type of medium of sensory experience. Based on personal accounts, dramatic performance and comics, our research derives from an attempt to understand the way in which the sensitive articulates itself with visual textualities produced by clothing. Furthermore, we intend to observe to what extent affection is present in the narratives formulated by our speakers. In this sense, it was crucial to this research a theoretical and methodological support related to an aesthetic perspective towards communications. Using an essayistic and self-reflective writing, this work indicates a dimension of appearance and the sensitive that configures a singular experience occurring in the body of the person who gets dressed, and also a perception that this experience happens in the encounter between bodies that share the same space.